PRADIGMA EPISTEMOLOGI PENDIDIKAN ISLAM (Kajian tentang Problematika dan Solusi Alternatif Epistemologi dalam Filsafat Pendidikan) - Dian Mego Anggraini (Akademika, 2018)
Abstract: The aim of this study is to discuss about the problem of epistemology of Islamic education that is not clear for still being considered following the epistemology of the West. The development of Islamic education and science still has an ambiguous attitude. Firstly, when looking at the findings of educational theories from the West and the East, it tends to be accepted without criticism by seeking arguments from the Quran and Hadith which sometimes tend to be irrelevant. Secondly, it is a very normative attitude in the face of the arguments of the Quran and Hadith instead of going through the stages of in-depth analysis. Both method and type of this study are commonly related to a study of literature, which displays the arguments of scientific reasoning that describe the results of literature review and researchers’ point of view concerning the epistemology of islamic education. Focus of the study is remain exploring and analyzing the problems and alternative solutions of epistemology in the Islamic education philosophy. This kind of study contains or delves into the idea of related propositions and should be supported by data or information obtained from literatures. With the foundation of qualitative and rationalistic philosophy. The results show that the epistemological approach requires a certain way or method, because it presents the process of knowledge of students rather than the result itself. This epistemological approach provides a complete understanding and skill. Those who know the process of any activity must know the outcome. Conversely, many know the outcome but do not know the process. Keywords: Epistemology, Islamic Education, problems and alternative solutions of epistemology